PENYUSUNAN PROFIL DESA KANDRIS SEBAGAI UPAYA PENGUATAN DATABASE DAN PERENCANAAN PEMBANGUNAN DESA KANDRIS, KECAMATAN BANUA LIMA, KABUPATEN BARITO TIMUR - Hussain, Abrar; Ulpah, Maria; Harlianto, Aldi; Marsya, Marsya; Hasanah, Uswatun; Vonsela, Daniel; Sidauruk, Judius Syahpala (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This service-learning program developed the Kandris 2025 Village Profile to address the lack of a comprehensive and updated village document. The goal is to create an integrated database on the population, geography, socio-economy, and potential of the village. The implementation methods included document studies, in-depth interviews with community leaders, and field observations. The result is a systematic and accurate profile document, which maps the objective conditions of the village in full. This document serves as a vital tool for the village government for data-driven development planning and increased transparency. Program sustainability is expected through periodic data updates and document digitization.